Beauty and preferences formation exemplified in the sports market - Hannah Josepha Rachel Altman; Morris Altman; Benno Torgler; Stephen Whyte (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Beauty has been used as a fast and frugal heuristic, and therefore an important determinant of choice, as highlighted in research by Hamermesh. In a world of asymmetric information, beauty represents a proxy for objective characteristics or an object of desire, according to an individual's preferences. A correlate of beauty, sexiness, has been used in sports to choose trainers or even to select the athletes expected to perform best, with people paying a premium for this beauty or sexiness. We argue that beauty can be a good or bad heuristic depending on the objective relationship between beauty and what it proxies. When it is a bad heuristic, it generates sub-optimal outcomes for sports organizations. We discuss the conditions under which the beauty or sexiness heuristic generates sub-optimal outcomes, why rational agents choose such a heuristic, and the conditions under which bad heuristics are sustainable. We also discuss this heuristic and the beauty premium in the context of Becker's economic theory of discrimination, wherein rational decision-makers trade-off material considerations for the utility gained by contracting beautiful and sexy individuals. The latter has implications for the economic sustainability of an organization.
Keywords: 330; Ästhetik; Heuristik; Sportmarketing; Asymmetrische Information; Präferenztheorie